DEVELOPMENT OF ENCEPHALITIS IN COVID DISEASE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In this article, the development of encephalitis in covid disease, prevention of the development of encephalitis, factors causing encephalitis in COVID-19 infection and its treatment are highlighted.